Can PBDE natural formation and degradation processes interfere with the identification of anthropogenic trends and sources? Evidences from sediments of the Nador Lagoon (Morocco). Issue 1 (15th July 2016) - Piazza, Rossano; Bellucci, Luca Giorgio; Giuliani, Silvia; Romano, Stefania; Frignani, Mauro; Pizzini, Sarah; Polo, Fabio Paolo; Vecchiato, Marco; Zambon, Stefano; El Moumni, Bouchta
Abstract: This paper presents the first results related to PBDE concentrations in sediments of the Nador Lagoon (N-E Morocco), an area endangered by different pollutant sources. Analyses were performed by HRGC-LRMS and confirmed by HRGC-HRMS on selected samples. Total surficial concentrations were 0.059–8.2 ng g − 1 . The maxima were found close to Nador City. Along the sedimentary records, the highest total concentrations (11 and 2.2 ng g − 1 ) were found at depths corresponding to times (1930s–1950s) when these chemicals were not yet produced. Dehydroxylation or demethoxylation of naturally occurring structural analogues of PBDEs under reducing conditions was suggested. BDE-47 dominated the congener compositions, while BDE-209, when present, could be detected only by HRGC-HRMS, proving that analytical degradation modified the original assemblage. Microbial anaerobic degradation could have changed congener compositions in sediments deposited from the 1970s to the 2000s. Current values are not harmful, but increasing trends call for constant monitoring. Graphical abstract: Highlights: For the first time, PBDEs were measured in sediments of the Nador Lagoon (Morocco). Total surficial values were higher near the urbanized area of Nador City. Natural formation could explain PBDEs at depths prior to the onset of production. Analytical degradation of BDE-209 was relevant under HRGC-LRMS conditions. Microbial anaerobic degradation at depth might have changed the original assemblage.